Model Revitalisasi Modal Sosial Guna Meningkatkan Pelaksanaan Fungsi Anggota Dewan Perwakilan Rakyat - Dahlan Dahlan; Yusra Yusra (Jurnal EMT KITA, 2018)
This study aims to find a model for revitalizing social capital in order to improve the implementation of the DPRD member functions in Aceh. The study was conducted on Members of the DPRA, the Banda Aceh DPRK, the Sabang DPRK, the Greater Aceh DPRK and the Pidie DPRK with a total of 206 legislative members. Data collection using questionnaires and then data analysis equipment using a structural equation model (SEM) which is operated with AMOS software. The study found that the personality and behavior of organizational citizenship behavior (OCB) had an important role in increasing the social capital of DPRD members which in turn had an impact on improving the supervisory function they carried out as legislators. OCB's personality and behavior also have a positive and significant impact on the implementation of the supervisory functions they carry out. The existence of social capital is able to mediate the influence of OCB personality and behavior and supervisory functions. The mediating effect of social capital as an intermediate variable is partial mediation.